ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN KSP.YOGA SOLAFIDE MANDIRI MEDAN - Windi Anggreny BR Sitompul; Yossi Fadly; Puja Rizqy Ramadhan (Ensiklopedia Education Review, 2022)
The problems in this study is whether the company's performance KSP.Yoga Solafide Mandiri has increased in the last five periods, namely the year 2015 to 2019 in terms of the financial statements. Purposes of conducting research is to determine the performance of the KSP.Yoga Solafide Mandiri seen from lUfuidity ratio, solvency ratios, activity ratios and profitability ratios. This type of research is based on the level of explanation namely descriptive study or re.search that aims to determine the performance of the financial .statements KSP.Yoga Solafide Mandiri with the use of financial ratio analysis. Ihe data used in this study are primary data in the form of financial statements information that consists of the Balance Sheet and Income Statement last five accounting. Calculating the financial ratios subsequently explained with informative sentence. The results showed that the financial condition KSP.Yoga Solafide Mandiri during 2015 through 2019 relatively well. This is due to the ability and a good performance management particularly in accounts receivable turnover, ability to achieve Ihe sales target, foresight to make consumer installment bills.Keywords: Financial Statements, Liquidity Ratios, Ratio Solvency, Activity Ratios, Profitability Ratio.